Spatio-temporal patterns of carbon, nitrogen and phosphorus in the aboveground parts of plants in alpine grasslands on the Qinghai-Xizang Plateau: Insights from a multi-faceted analysis. - Guangyu Zhang; Wei Sun; Shaowei Li; Zhiming Zhong; Gang Fu (PLoS ONE)
Uncertainties in spatio-temporal patterns of nitrogen, phosphorus, especially carbon of the aboveground parts of plants limit our predictions of plant carbon sequestration capacity, nitrogen and phosphorus cycling. This study quantified the spatio-temporal patterns of carbon, nitrogen and phosphorus in the aboveground parts of plant communities in alpine grasslands of the Qinghai-Xizang Plateau in 2000-2022. The spatially averaged carbon content, nitrogen content, phosphorus content, carbon pool, nitrogen pool, phosphorus pool, carbon-nitrogen ratio, carbon-phosphorus ratio and nitrogen-phosphorus ratio were 29.96%, 1.56%, 0.32%, 28.44 g C m-2, 0.82 g N m-2, 0.07 g P m-2, 30.39, 271.16 and 9.59, respectively. Climate change and human activities jointly led to increases of 0.71%, 0.28%, 10.28%, 11.05%, 10.29%, 2.36%, 8.46% and 0.42% in the spatially averaged carbon content, nitrogen content, carbon pool, nitrogen pool, phosphorus pool, carbon-nitrogen ratio, carbon-phosphorus ratio and nitrogen-phosphorus ratio, while resulting in a 1.64% decrease in the phosphorus content. There were no relationships between the changes of carbon, nitrogen and phosphorus and their temporal stability. Under the influence of pure climate change, the changes of nitrogen and phosphorus pools decreased with the increase of nitrogen and phosphorus pools. Under the influence of pure human activities, the changes of nitrogen and phosphorus contents decreased with the increase of nitrogen and phosphorus contents. Therefore, the average carbon content of the aboveground parts of plant communities was < 45%, which was related to the unique climate and soil conditions of the Qinghai-Xizang Plateau. The greater the temporal stability of plant carbon, nitrogen and phosphorus, the relative change was not always smaller, which might be because the changes of plant carbon, nitrogen and phosphorus were also affected by other factors (e.g., species competition). Climate change homogenized the spatial distribution of nitrogen and phosphorus pools, and human activities homogenized the spatial distribution of nitrogen and phosphorus contents.